2003
DOI: 10.1021/ja034624r
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oriented Self-Assembled Monolayers as Templates for Epitaxial Calcite Growth

Abstract: The lateral alignment of [012] habit-modified calcite crystals with respect to a carboxylic acid terminated self-assembled monolayer (SAM) of thiols has been determined. The crystals were grown from a Kitano solution (pH 5.6-6.0), and the samples were investigated with scanning electron microscopy, X-ray diffraction, and polarization microscopy. For the first time, a lattice match in one direction, which is the nearest neighbor direction of the SAM and the calcite <100> direction, has been experimentally shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 19 publications
5
128
0
Order By: Relevance
“…None of other polymorphs of calcium carbonate were formed, on the contrary to what has been observed on the first substrate studied. It is important to note here that epitaxial formation of calcite crystals has already been detected for gold and silver but with the use of templates [16][17][18][19][20].…”
Section: On Polycrystalline Goldmentioning
confidence: 94%
See 1 more Smart Citation
“…None of other polymorphs of calcium carbonate were formed, on the contrary to what has been observed on the first substrate studied. It is important to note here that epitaxial formation of calcite crystals has already been detected for gold and silver but with the use of templates [16][17][18][19][20].…”
Section: On Polycrystalline Goldmentioning
confidence: 94%
“…Recently, a range of strategies has been explored to control nucleation and growth [15,16] of CaCO 3 crystals based on molecular recognition at interfaces. These methods include template-directed nucleation using self-assembled monolayers (SAMs) of alkanesthiols terminated with an acid functional group (CO 2 H or SO 3 H) which is used to induce face-selectivity [16][17][18][19][20] for calcite. These studies have shown the great potential of using supramolecular templates to regulate crystallization, but the faceselectivity of nucleation on those organic surfaces is generally limited by the defects presented by the SAM structure [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the biomimetic study of calcium carbonate crystallization on ordered substrates has attracted attention. The later crystallizations of calcium carbonate on Langmuir films or self-assembled monolayers (SAM) provide many good examples of the template effect on oriented crystallization [69,[104][105][106][107]. The template effect usually refers to the geometric or stereochemical match between a final crystal face and an organic matrix.…”
Section: Biomimetic Organic Matrixmentioning
confidence: 99%
“…Oriented calcite with alignment of {012} face has been also obtained by using self-assembled monolayer (SAM) functionalized with carboxylic group using Kitano crystallization method (22) . In addition, XRD patterns of CaCO 3 after crystallization using poly(KAMPS) shows {104} face at 2θ = 29,4° as the most intense peaks confirming the calcite (data no shown).…”
Section: Resultsmentioning
confidence: 99%